The Role and Current Status of IFRS in the Completion of National Accounting Rules – Evidence from Romania. (4th May 2017) - Albu, Cătălin Nicolae; Albu, Nadia
Abstract: Romanian accounting rules (RAR) had followed a convergence process with International Accounting Standards/International Financial Reporting Standards (IAS/IFRS) since 1999, and the level of convergence has increased over time. The Romanian accounting regulator continues to follow IAS/IFRS in internalizing the Accounting Directive2013 /34/EU. Only a few major differences still exist (some of them due the restrictions in the Accounting Directive2013 /34/EU) between RAR and IFRS. However, RAR lack the level of detail existing in IFRS, and IFRS cannot be used in practice as a source of guidance and interpretation. While major stakeholders have a positive attitude towards the convergence with IAS/IFRS, the Romanian accounting regulator intends to keep the control over RAR and avoid differences in interpretations that might have tax consequences. Despite the good level of convergence of RAR with IFRS, practitioners tend to continue to utilize the tax approach as a source of guidance and interpretation.